1996
DOI: 10.1034/j.1399-3054.1996.960119.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase profiles in mature carrot (Daucus carota) roots and purification and characterization of a novel isoform

Abstract: mature carrot (Daueus carota) roots and purification and characterization of a novel isoform. -Physiol. Plant. 96: 130-138,The profile of cMtinases (EC 3.2.1,14) in mature carrot {Daucus carota L. cv. Eagle) roots was studied. Multiple chitinase bands (8-10) were observed in native and sodium dodecylsulfate-denaturing polyacrylamide gels. The molecular masses of these chitinases were estimated to be from 20 000 to 40 000. One major chitinase was purified and found to be an acidic protein with pi at 4,3 and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Pure chitinase was isolated from sugar beet leaves with relatively high recovery of activity ( 27.4%) as compared to that of soybean seeds and cabbage stem (12%) and (18%) isolated by Wadsworth and Zikakis (1984) and Chang et al (1996) respectively, but lower than those from thorn apple (48%) (Broekaert et al, 1988). The optimum pH for chitinase activity from sugar beet was measured to be 4.5 which are in accordance to those reported by Wadsworth and Zikakis (1984), Kono et al (1990) and Zhang et al, (1996) for soybean seeds Japanese eel and carrot roots chitinase respectively. While Molano et al (1979) and Chang et al (1996) isolated chitinase from wheat grain and cabbage stem with an optimum pH 6.0.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Pure chitinase was isolated from sugar beet leaves with relatively high recovery of activity ( 27.4%) as compared to that of soybean seeds and cabbage stem (12%) and (18%) isolated by Wadsworth and Zikakis (1984) and Chang et al (1996) respectively, but lower than those from thorn apple (48%) (Broekaert et al, 1988). The optimum pH for chitinase activity from sugar beet was measured to be 4.5 which are in accordance to those reported by Wadsworth and Zikakis (1984), Kono et al (1990) and Zhang et al, (1996) for soybean seeds Japanese eel and carrot roots chitinase respectively. While Molano et al (1979) and Chang et al (1996) isolated chitinase from wheat grain and cabbage stem with an optimum pH 6.0.…”
Section: Discussionsupporting
confidence: 75%
“…Concerning the M,s of chitinase enzyme isolated from different sources, it was found to be different, as chitinase isolated from bean leaves, soybean seeds, cabbage stem with root and tomato stem tissue have M,s range from 27×10 3 to 31×10 1 Dalton (Pegg and Young, 1982;Wadsworth and Zikakis, 1984;Chang et al, 1996). It was found that the M,s of stomach of Japanese eel, Bacillus, cereus, Serratia marcescens and S. peculiarities chitinase were 59×10 3 , 68.52×10 3 , 58×10 3 and 45×10 3 Dalton respectively (Kono et al, 1990;Zhang et al, 1996: Porfir'eva et al, 1997.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitinase is more stable than laminarinase A and laminarinase B when heated up to 50°C for 60 min. Similarly, chitinase from carrot roots was relatively stable when heated at temperatures below 60°C (Zhang et al, 1996), while Laminarinase from soybean and Nicotiana glutinosa leaves, were inactivated at 65°C (Moore and Stone, 1972a;Keen and Yoshikawa, 1983). The complete inhibition of chitinase with some heavy metals CuSQ 4 , Hg (NO 3 ) 2 , CuCl 2 , CaCl 2 and MgCl 2 and laminarinase A with K 2 SO 4 and Hg (NO 3 ) 2 could be related to the creation of the cation to chitin or laminarin A subkratesin turn cleavage or hydrolysis of substrates by the enzymes could be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Among the PR proteins, chitinases, glucanases and osmotins expressed in plants attacked by fungi are thought to limit fungal growth. This antifungal biological function has been demonstrated in vitro against several fungi (Anfoka and Buchenauer, 1997;Ji and Kie, 1996;Lawrence et al, 1996;Yun et al, 1996;Zhang et al, 1996). The hydrolases, chitinase and glucanase which degrade the ß-1,4-linkage between N-acetylglucosamine residues of chitin and glucans in fungal cell walls, and thaumatin-like proteins are also known to be induced in plants by adverse environmental factors (Bowles, 1990;Cruz-Ortega and Ownby, 1993;Hincha et al, 1997;Yalpani et al, 1994).…”
mentioning
confidence: 97%